Hubungan Indeks Kepuasan Pasien tentang Mutu Pelayanan Dimensi Kehandalan dengan Minat Berobat Kembali di RSD Kalisat Kabupaten Jember - Davina Amalia; Dwita Aryadina Rachmawati; Hairrudin Hairrudin (Pustaka Kesehatan, 2018)
RSD Kalisat is one of the hospital that is very concern with the quality of health services. The reliability of service quality is often perceived as the most important dimension for the customer. Quality of service is very influential on patient satisfaction. If the health care provided is good, then the patient will be satisfied and the possibility to reuse services in health care-related agencies will increase. The purpose of this study was to determine the correlation between patient satisfaction index in the reliability of service quality with utility at RSD Kalisat. This study used cross sectional design with total sample of 84 respondents. The instrument used was RSD Kalisat profile and questionnaire to determine patient satisfaction index in the reliability of service quality and statement for utility. The results of statistical test by Spearman's Rho showed a significance value (p=0.021) and the correlation coefficient (r =0.252). Thus, it can be concluded that there was a significant correlation between patient satisfaction index in the reliability of service quality with utility at RSD Kalisat Jember with a weak correlation. Keywords: index satisfaction, reliability, service quality, utility